Ultrasonographic evaluation of anatomical variations, of the first dorsal compartment of wrist, and its correlation with de Quervain’s disease recurrence in Indian population: a hospital based longitudinal study - Mukherjee, Soutrik; Roy, Amlan J.; Mandal , Prasun (International Journal of Research in Orthopaedics, 2023)
Background: de Quervain’s disease is a commonly encountered debilitating condition mostly treated conservatively. Cadaveric studies have revealed anatomical variations in the first dorsal compartment of the wrist; however, a causal association between the variants and recurrence of the disease has not been established. An ultrasonographic assessment of the first dorsal compartment of the wrist was done, to correlate the response to treatment, of the different anatomical variants. Methods: 106 wrists were included in the study after clinically confirming de Quervain’s disease. All were injected with 20mg of methylprednisolone acetate in the first dorsal compartment of the wrist and were followed up. Patients who were pain free for at least six months, as well as patients who did not respond or had a recurrence of disease within eight to twelve weeks, were all assessed with ultrasound. Results: 57.54% of the wrists were cured with one injection most of which revealed a tendon arrangement of one abductor pollicis longus (APL) and one extensor pollicis brevis (EPB) and two APL and one EPB without any septation. 32.07% of the wrists did not respond to this treatment and most of them comprised of septations and aberrant compartments with presence of supernumerary tendons. Conclusions: Ultrasonographic assessment of the first dorsal compartment of wrist, of all patients suffering from de Quervain’s tenosynovitis must be done to predict the outcome of conservative therapy and customize an optimal treatment modality for the individual anatomical variant.